(untitled) (Scientific journal of the Fergana State University, 2025)
The article analyzes relevant methods for teaching Russian as a foreign language. Particular attention is paid to communicative and interactive approaches, the use of modern technologies, and the individualization of the educational process. Key aspects that enhance the quality of education and foster the development of students’ intercultural skills are highlighted.